Assessing blink reflex circuits by three different afferent routes in Parkinson's disease. Issue 4 (April 2019) - Weise, David; Pargac, Clemens; Pelz, Johann Otto; Rumpf, Jost-Julian; Fricke, Christopher; Classen, Joseph
Highlights: Establishment of new blink reflex variant by stimulation of the auricular branch of the vagus nerve. Testing of blink reflex variants elicited by three different afferents in PD. No evidence for malfunctioning of differential neural brainstem circuits in PD. Abstract: Objective: Degeneration of nuclei of the brainstem, especially parts of the vagal nuclei complex and the reticular formation, in Parkinson's disease (PD) may in part be responsible for nonmotor signs like obstipation, cardiac dysfunction and rapid eye movement sleep behavior disorder (RBD). The aim of the study was to establish a new blink reflex (BR) variant involving the vagal nuclei complex and the reticular formation and to investigate BR comprehensively using 3 different afferent routes in PD. Methods: In this cross-sectional observational study in 30 PD patients and 30 age and sex matched healthy controls, BR was elicited by stimulation of the auricular branch of the vagus nerve (ABVN) and compared to conventional BR variants evoked by the trigeminal and median nerve. Results: BRs could be elicited reliably by stimulation of ABVN in both groups. In none of the three BR variants, latencies or amplitudes differed between PD patients and controls. In PD, BR parameters were not related to cognition or presence of RBD. Conclusion: The present study did not provide evidence for malfunctioning of neural circuits subserving BRs elicited by three different afferents in PD. Significance: Brainstem circuits mediating these BR variants may be spared from neurodegeneration in PD.